Association of Premature Androgenetic Alopecia and Metabolic Syndrome in a Young Indian Population - Chakrabarty, S (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Although evidences for association of androgenetic alopecia (AGA) with metabolic syndrome (MetS) are accruing, inconclusiveness with respect to the gender specificity and differential association of MetS with increasing severity of AGA continues to persist. Furthermore, data specific to Indian settings are relatively sparse. AIMS: The present study aimed at assessing the frequency of MetS in individuals with early AGA in Indian settings. SETTINGS AND DESIGN: A case-control study was conducted at a trichology clinic in Bengaluru between April 2012 and September 2012 with a total of 85 cases of AGA and 85 age-matched controls. MATERIALS AND METHODS: The Norwood-Hamilton classification was used to assess the grade of AGA. MetS was defined according to the National Cholesterol Education Program Adult Treatment Panel III criteria. Blood pressure, blood glucose, lipid parameters, and body mass index along with anthropometric measurements were assessed in all study participants. STATISTICAL ANALYSIS USED: Chi-square test was used to compare proportions between groups. Means were compared between groups using Student's t-test. RESULTS: MetS was seen in a higher proportion of patients with AGA (43.5%) as compared to the control group (2.4%) and the differences were statistically significant (P < 0.001). As compared to controls, patients with AGA had higher triglycerides (P < 0.001), systolic blood pressure (P < 0.001), diastolic blood pressure (P < 0.001) along with significantly lower high-density lipoprotein cholesterol levels (P < 0.001). Severity of AGA was not associated with MetS. CONCLUSIONS: AGA is associated with MetS in male Indian patients aged <30 years. Studies with large sample sizes may be required to conclusively define any putative associations between AGA grades and MetS.